School Memories of Preservice Teachers: An Analysis of Their Role in the Conceptions About the Relationships Between Emotions and Teaching/Learning Processes - Bächler, Rodolfo; Salas, Romina (Frontiers in Psychology, 2021)
Abstract With the aim of exploring the role of emotional elementary school memories that preservice teachers have, in their conceptions about the relationships between emotions and teaching- learning processes, a study was carried out. The sample consisted of all first-year preservice teacher from one campus of a public university which will be revealed when the article is published (167 students). The study used a mixed method research, specifically, according to the typology established by Leech & Onwuegbuzie (2009), it is a partially mixed design, sequential (composed of two research stages), with equal status design (P3). In the first part (quantitative), the conceptions of the preservice teachers were evaluated by means a dilemma questionnaire. In the second part (qualitative), a retrospective imagery was applied to a subgroup of thirty participants from the total sample with the aim of detecting and analyzing emotionally significant memories of teaching-learning situations in elementary school. The result of the first part of the study showed that most of preservice teachers maintain conceptions that separates affect and cognition as non-integrated processes. The results of the second part revealed that preservice teachers remember different types of experiences, most of them are associated with the characteristic and behavior from their primary school teachers. Finally, the recovered memories were analyzed in terms of their relationship with conceptions, concluding that having experienced fear in school could be a factor related to the type of conceptions held.